Hubungan Sifat Sifat Fisik Tanah Yang Dicampur Dengan Kapur Terhadap Stabilitas Tanah Lempung Pada Tanggul - Idrus, S. Tantri Handayani; Iswan, I; Syah, Aminudin (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
In embankment planning, it is necessary to consider the influencing factors such as the materialfor making the embankment, slope stability, guard height, slope protection, the width of theembankment, the slope and dumping facilities. Some areas in Indonesia do not have good qualitysoil. For instance, the soil in Palembapang Village, Kalianda, South Lampung. Regarding theissues, soil maintenance is mandatory to be done to increase the physical parameters of the soil sothat the carrying capacity of the soil is maintained. The results shows that at the mixture rate of0%, 4%, 8%, 12% and 16%, the lime is classified as CL (clay low plasticity)which indicates nonorganicclay with low to medium plasticity. The lab testing result of the sample of natural soilshows cohesion value of 0,1813 kg/cm2 and shear angle value of 20o. After stabilizing processwas done using additives, the cohesion value and shear angle value were significantly increasing.It proves that lime can increase soil density as both value increased. In the natural soil sample,the value of the safety factor was still below the safe limit. Another lime additive was added to thesoil sample with lime addition of 16%. None of the safety factor limits were below average afterthe process. In conclusion, lime additive can decrease the plasticity (liquid limit and plasticityindex), enhancing strength and durability, reducing water absorption and soil development aswell as strengthening the stability of the embankment.